Plasma Matrix Metalloproteinase-9 Response to Downhill Running in Humans - Welsh, M. C.; Allen, D. L.; Byrnes, W. C. (International Journal of Sports Medicine, 2014)
Matrix metalloproteinase-9 is a proteolytic enzyme capable of degrading proteins of the muscle extracellular matrix. Systemic levels of MMP-9 or its inhibitor, tissue inhibitor of metalloproteinase-1 (TIMP-1), have the potential to serve as blood markers of exercise-induced muscle damage. The purpose of this study was to determine if an eccentrically-dominated task, downhill running (DHR), produces changes in plasma MMP-9 or TIMP-1 and examine the relationship between MMP-9/TIMP-1 levels and indirect indicators of muscle damage. Subjects were sedentary (SED, n=12) or had a history of concentrically-biased training (CON, n=9). MMP-9 and TIMP-1 were measured before (Pre-Ex), immediately after (Post-Ex), and 1-, 2-, 4-, and 7-days post-DHR (−10°), and compared to discomfort ratings, creatine kinase activity and strength loss. At 1-day Post-Ex, discomfort increased (5.6±7.8 to 45.5±19.9 mm; 0–100 mm scale), strength decreased (−6.9±1.6%) and CK increased (162.9±177.2%). MMP-9 was modestly but significantly increased at Post-Ex in both CONC and SED (32.7±33.6%) and at 4-days in SED (66.9±88.1%), Individual responses were variable, however. There were no correlations between MMPs and discomfort ratings, plasma CK or strength. While plasma MMP-9 changes may be detectable in the systemic circulation after DHR, they are small and do not correspond to other markers of damage.
Keywords: eccentric exercise; muscle damage; muscle injury; extracellular matrix; gelatinase-B; concentric training